Interictal localization of the epileptogenic zone: Utilizing the observed resonance behavior in the spectral band of surrounding inhibition - Alamoudi, Omar A.; Ilyas, Adeel; Pati, Sandipan; Iasemidis, Leon (Frontiers in Neuroscience, 2022)
The gold standard for epileptogenic zone (EZ) continues to be the visual inspection of electrographic changes around seizures’ onset by experienced electroencephalography (EEG) readers. Development of an epileptogenic focus localization tool that can delineate the EZ from the analysis of interictal (seizure-free) period is still an open question of great significance for improved diagnosis (e.g., presurgical evaluation) and treatment of epilepsy (e.g., surgical outcome). We developed an EZ interictal localization algorithm (EZILA) based on novel analysis of intracranial EEG (iEEG) using a univariate periodogram-type power measure, a straight-forward ranking approach, a robust dimensional reduction method and a clustering technique. Ten patients with temporal lobe and extra temporal lobe epilepsies and matching the inclusion criteria (Engel Class I ≥ 12 months post-surgery) were recruited in the epilepsy monitoring unit (EMU) at the University of Alabama Medical Center. In a nested k-fold cross validation statistical framework, EZILA assigned the highest score to iEEG channels within the EZ in all these patients (10/10) during the first hour of the iEEG recording and up to their first typical clinical seizure in the EMU (i.e., early interictal period). To further validate EZILA’s performance, data from two new (Engel Class I) patients were analyzed in a double-blinded fashion; the EZILA successfully localized iEEG channels within the EZ in both patients. Out of the sampled brain regions, iEEG channels in the EZ were most frequently and maximally active in seizure-free (interictal) periods across patients in specific narrow gamma frequency band (~ 60 to 80 Hz), which we have termed focal frequency band (FFB). These findings are consistent with the hypothesis that the EZ may interictally be regulated by inhibitory neurons with resonance property within that narrow gamma band. In conclusion, EZILA achieved reliable localization of sites within the EZ in patients with focal epilepsy of different types (temporal and extra-temporal) when proper analysis is conducted, within specific FFB and during the early interictal period in the EMU.